Adolescent gender differences in neural reactivity to a friend's positive affect and real-world positive experiences in social contexts. (June 2020) - Alarcón, Gabriela; Morgan, Judith K.; Allen, Nicholas B.; Sheeber, Lisa; Silk, Jennifer S.; Forbes, Erika E.
Highlights: Males reported more recent happy occasions with class/teammates than females. Males activated fusiform gyrus more than females while viewing unfamiliar peers. Striatum functional connectivity mediated gender differences in social behavior. Abstract: Peers become increasingly important during adolescence, with emerging gender differences in peer relationships associated with distinct behavioral and emotional outcomes. Males tend to socialize in larger peer groups with competitive interactions, whereas females engage in longer bouts of dyadic interaction with more intimacy. To examine gender differences in neural response to ecologically valid displays of positive affect and future social interactions, 52 adolescents (14–18 years old; female = 30) completed a social reward functional magnetic resonance imaging (fMRI) task with videos of a same-gender best friend (BF) or unfamiliar peer (UP) expressing positive (versus neutral) affect. Participants completed ecological momentary assessment of social experiences for two 5-day intervals. Compared with females, males more often reported that their happiest experience in the past hour occurred with class/teammates. Females and males displayed greater fusiform gyrus (FG) activation during BF and UP conditions, respectively ( p voxel <0.0001, p cluster <0.05, family-wise error). Compared with males, females exhibited greater nucleus accumbens (NAcc)-precuneus functional connectivity to BF Positive> UP Positive. An exploratory analysis indicated that the association of male gender with a greater proportion of positive experiences with class/teammates was statistically mediated by greater NAcc-precuneus functional connectivity. Gender differences in positive social experiences may be associated with reward and social cognition networks.